Peningkatan Kualitas Hidup Lansia melalui Program KULO: Penerapan Model Edukasi dan Praktik Pertanian Sederhana - Salu Azahra Putri; Hannety Dea Aghny Shyfa; Muhammad Luthful Hakim; Fatih Ardiansyah; Sofia Balqis Khoirunnisa; Nasywa Atika Aura Putri; Rizky Maulana Akbar Firdaus; Muhammad Raihan Ghifari; Elisa Sabrina Gunawan; Galuh Putri Alzira; Nisa Rachmania Mubarik (Jurnal Pusat Inovasi Masyarakat, 2026)
The elderly represent a demographic highly vulnerable to physical and psychosocial decline, which often leads to diminished involvement in productive activities, particularly within rural environments. To address this, the KULO Program (Optimistic Elderly Superior Garden) was established to empower senior citizens through community-based horticultural farming, aimed at enhancing their skills, independence, and overall quality of life. Implemented in Padukuhan Teguhan, Wunung Village, in collaboration with the Seger Waras Elderly Family Development (BKL) group, the program utilizes polybag cultivation for commodities like Capsicum annuum L. (red chili pepper) and Solanum melongena L. (purple eggplant). This participatory model integrates fundamental agricultural education with direct practical experience, utilizing a growth medium of soil, compost, and charred husks. With 58 elderly participants actively engaged in every stage, the results demonstrate that polybag farming is an exceptionally effective method for supporting both physical and social engagement. Participants reported significant improvements in technical proficiency, self-confidence, and a renewed sense of communal solidarity. While the program faced hurdles such as limited mobility and low literacy levels, an adaptive approach characterized by intensive cadre mentoring and observational learning-ensured that all empowerment goals were met. Beyond strengthening local food security, KULO enriches the lives of the elderly through meaningful, contributive actions involving various stakeholders. Given its success, the KULO Program holds great potential for replication in other communities with similar characteristics. Ensuring its long-term sustainability will require consistent policy support, regular training for cadres, and seamless integration into routine community activities, solidifying KULO as an adaptive, practical, and sustainable model for elderly empowerment.